The effect of fatigue severity on job performance : research on aircraft maintenance technicians - İlhan, Özge (My University, 2022)
Yorgunluk, günümüzde özellikle havacılık sektöründe sıklıkla rastlanılan bir durum olmaya başlamıştır. Yorgunluğun etkilediği birçok faktör bulunmakta olup, yorgunluğun uçak bakım teknisyenlerine yönelik bir uygulama ile işyerinde göstermiş olduğu iş performans ile arasında ilişki tespit edilmesi amaçlanmaktadır. Ayrıca bu çalışmada uçak bakım teknisyenlerinin demografik değişkenlere göre yorgunluk ve iş performansı düzeylerinin farklılık durumları da belirlenecektir. Havacılık sektöründe çalışan 283 uçak bakım teknisyenine Yorgunluk Şiddet Ölçeği ve İş Performansı ölçeğinden oluşan veri toplama araçları ile uygulanan anketlerle sonuçların gözlemlenmesi amaçlanmıştır. Araştırmanın sonucu SPSS program ile analiz edilmiştir. Araştırmada bağımsız t-test, tek yönlü anova, regresyon analizi, faktör analizi ve pearson korelasyon yöntemleri kullanılmıştır. Ayrıca havacılık sektöründe çalışan uçak teknisyenlerinin bazı demografik özelliklerine göre yorgunluk şiddeti ve iş performansı algısının farklılaştığı belirlenmiştir. Hipotez testleri sonucu, yorgunluk şiddeti ile iş performansı ve görev performansına verilen önem arasında anlamlı ilişki olduğunu gösterirken, yorgunluğun bağlamsal performans üzerinde anlamlı ilişki olmadığını ortaya koymuştur.

Fatigue has started to be a frequently happened situation, especially in the aviation industry. There are many factors that fatigue affects, and it is aimed to determine the relationship between fatigue and job performance in the workplace with a practice for aircraft maintenance technicians. In addition, in this study, differences in fatigue and job performance levels of aircraft maintenance technicians according to demographic variables will also be determined. It was aimed to observe the results with the questionnaires applied to 283 aircraft maintenance technicians working in the aviation industry with the data collection methods consisting of the Fatigue Severity Scale and the Job Performance scale. The results of the research were analyzed with the SPSS program. Independent t-test, one-way anova, regression analysis, factor analysis and Pearson correlation methods were used in the research. In addition, it was determined that the severity of fatigue and job performance perception differed according to some demographic characteristics of aircraft technicians working in the aviation industry. The results of the hypothesis tests showed that there was a significant relationship between the severity of fatigue and the importance of job performance and task performance, while there was no significant relationship between fatigue on contextual performance.
Keywords: Aviation Sector; Business; Fatigue Severity; Havacılık Sektörü Job Performance; İş Performansı; İşletme; Yorgunluk Şiddeti